Person-centred experiential therapy versus cognitive behavioural therapy delivered in the English Improving Access to Psychological Therapies service for the treatment of moderate or severe depression (PRaCTICED): a pragmatic, randomised, non-inferiority trial. (June 2021) - Barkham, Michael; Saxon, David; Hardy, Gillian E; Bradburn, Mike; Galloway, Deanna; Wickramasekera, Nyantara; Keetharuth, Anju D; Bower, Peter; King, Michael; Elliott, Robert; Gabriel, Lynne; Kellett, Stephen; et al.
Summary: Background: The UK Government's implementation in 2008 of the Improving Access to Psychological Therapies (IAPT) initiative in England has hugely increased the availability of cognitive behavioural therapy (CBT) for the treatment of depression and anxiety in primary care. Counselling for depression—a form of person-centred experiential therapy (PCET)—has since been included as an IAPT-approved therapy, but there is no evidence of its efficacy from randomised controlled trials (RCTs), as required for recommendations by the National Institute for Health and Care Excellence. Therefore, we aimed to examine whether PCET is cost effective and non-inferior to CBT in the treatment of moderate and severe depression within the IAPT service. Methods: This pragmatic, randomised, non-inferiority trial was done in the Sheffield IAPT service in England and recruited participants aged 18 years or older with moderate or severe depression on the Clinical Interview Schedule-Revised. We excluded participants presenting with an organic condition, a previous diagnosis of personality disorder, bipolar disorder, or schizophrenia, drug or alcohol dependency, an elevated clinical risk of suicide, or a long-term physical condition. Eligible participants were randomly assigned (1:1), independently of the research team, and stratified by site with permuted block sizes of two, four, or six, to receive either PCET or CBT by use of a remote, web-based system that revealed therapy after patient details were entered. Those assessing outcomes were masked to treatment allocation. Participants were seen by appropriately trained PCET counsellors and CBT therapists in accordance with the IAPT service delivery model. Depression severity and symptomatology measured by the Patient Health Questionnaire-9 (PHQ-9) at 6 months post-randomisation was the primary outcome, with the PHQ-9 score at 12 months post-randomisation being a key secondary outcome. These outcomes were analysed in the modified intention-to-treat population, which comprised all randomly assigned patients with complete data, and the per-protocol population, which comprised all participants who did not switch from their randomised treatment and received between four and 20 sessions. Safety was analysed in all randomly assigned patients. The non-inferiority margin was set a priori at 2 PHQ-9 points. Patient safety was monitored throughout the course of therapy, adhering to service risk procedures for monitoring serious adverse events. This trial is registered at the ISRCTN Registry, ISRCTN06461651, and is complete. Findings: From Nov 11, 2014, to Aug 3, 2018, 9898 patients were referred to step three treatments in the Sheffield IAPT service for common mental health problems, of whom 761 (7·7%) were referred to the trial. Of these, we recruited and randomly assigned 510 participants to receive either PCET (n=254) or CBT (n=256). In the PCET group, 138 (54%) participants were female and 116 (46%) were male, and 225 (89%) were White, 16 (6%) were non-White, and 13 (5%) had missing ethnicity data. In the CBT group, 155 (61%) participants were female and 101 (39%) were male, and 226 (88%) were White, 17 (7%) were non-White, and 13 (5%) had missing ethnicity data. The 6-month modified intention-to-treat analysis comprised 401 (79%) of the enrolled participants (201 in the PCET group; 200 in the CBT group) and the 12-month modified intention-to-treat analysis comprised 319 participants (167 in the PCET group; 152 in the CBT group). The 6-month per-protocol analysis comprised 298 participants (154 in the PCET group; 144 in the CBT group). At 6 months post-randomisation, PCET was non-inferior to CBT in the intention-to-treat population (mean PHQ-9 score 12·74 [SD 6·54] in the PCET group and 13·25 [6·35] in the CBT group; adjusted mean difference −0·35 [95% CI −1·53 to 0·84]) and in the per-protocol population (12·73 [SD 6·57] in the PCET group and 12·71 [6·33] in the CBT group; 0·27 [95% CI −1·08 to 1·62]). At 12 months post-randomisation, there was a significant adjusted between-group difference in mean PHQ-9 score in favour of CBT (1·73 [95% CI 0·26–3·19]), with a 95% CI exceeding the 2-point non-inferiority margin. There were two deaths, one death by suicide in the PCET group and one due to chronic obstructive pulmonary disease in the CBT group. Both were assessed by the responsible clinician to be unrelated to the trial. In terms of using emergency departments for depression-related events, four people (three in the PCET group; one in the CBT group) made more than a single use and six people (three in the PCET group; three in the CBT group) made a single use. One patient in the PCET group had inpatient treatment for a depression-related event. Interpretation: This trial is the first to examine the two most frequently administered psychological therapies in the IAPT service. The finding of non-inferiority of PCET to CBT at 6 months supports the results from large, routine, non-randomised datasets from the IAPT programme. Given the high demand for psychological therapies and the need for patient choice, our findings suggest the need for continued investment in the training and delivery of PCET for improving short-term outcomes, but suggest that PCET might be inferior to CBT at 12 months. Funding: British Association for Counselling and Psychotherapy Research Foundation.